TORAKOCHIRURGIAThe results of surgical treatment of pulmonary aspergilloma - Gabryel, Piotr; Piwkowski, Cezary; Kasprzyk, Mariusz; Zieliński, Paweł; Dyszkiewicz, Wojciech (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2009)
Introduce: The most common indication for operative treatment of pulmonary aspergilloma is massive haemoptysis. The operative treatment is demanding and frequently requires extensive pulmonary decortication. This leads to a risk of significant blood loss and prolonged air leak. Aim: Retrospective analysis of the results of operative treatment of pulmonary aspergilloma including intraoperative technical difficulties and postoperative complications. Material and Methods: In the years 2000-2009 forty-two patients underwent 43 procedures for pulmonary aspergilloma. 31 lobectomies, 8 wedge resections, 2 pneumonectomies, 1 bilobectomy and 1 cavernoscopy with cavernostomy were performed. We analysed risk factors, indications for treatment, type of procedure, morbidity and mortality. Results: There was no perioperative mortality. Three patients died in the postoperative period. Prolonged air leak (> 7 days) was encountered in 5 patients and 1 of these patients required thoracotomy. Residual air space was present in 10 patients (23%). Mean hospital stay was 20.2 days (from 7 to 56 days). Conclusions: 1. The main indication for surgical treatment of pulmonary aspergilloma is massive haemoptysis but the operations under those conditions lead to increased morbidity and mortality. 2. Extensive decortication of the lung increases the number of patients with postoperative bleeding and the need for rethoracotomy. 3. Postoperative air leak and residual pleural space requires prolonged chest tube drainage, but the need for surgical treatment is seldom.